DISTRIBUTIONAL BOUNDARY VALUE OF THE BLASCHKE PRODUCT - Pandeski, Nikola; Manova-Eraković, Vesna (Matematichki Bilten, 2005)
In this paper we found the distributional boundary value of the Blaschke product in the upper half plane.